Counseling and the human predicament a study of sin, guilt, and forgiveness - Aden, Leroy; Benner, David G. (Grand Rapids, MI Baker, 1989)
Includes bibliographical references and index.
Keywords: Pastoral counselling; Christianity -- psychology; Man (Christian theology).; Forgiveness of sin -- theology